PENGARUH LEVERAGE, PROFITABILITAS, DAN UKURAN PERUSAHAAN, TERHADAP KEBIJAKAN DIVIDEN PADA SUB SEKTOR INDUSTRI SEMEN DAN SUB SEKTOR INDUSTRI OTOMOTIF TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2008-2015 - Rilla Gantino; Fahri Muhammad Muhammad Iqbal (Jurnal Riset Akuntansi dan Bisnis, 2017)
Based on the existing data in Indonesia Stock Exchange during period 2008-20015, it can be seen that there is still a sub-company of the automotive sector is not paying it’s dividend. This research also tried to reveal the significant level leverage ( debt to equity ratio), profitability (net profit margin),and firm size ( total asset) to the deviden policy. The sampling method used is purposive sampling. This research consists of 4 companies of cement sub-sector and 6 companies of automotive sub-sector which registered in Indonesia Stock Exchange from total population 6 companies of cement sub-sector and 13 companies of automotive sub-sector. The type of data is secondary data obtained from the financial statements and annual reports. Data analysis method used is multiple linear regression analysis. The result showed that simultantly leverage, profitability, firm size have a significant effect on deviden policy in cement industry and automotive industry. Partially, in cement industry only firm size that affected significantly toward deviden policy, but leverage and profitability are affected but not significant toward deviden policy. In automotive industry only leverage that affected significantly toward deviden policy, but profitability and firm size are affected but not significant toward deviden policy